Evaluation of castor trait specific inbred lines under rainfed alfisols of Ananthapuramu: Evaluation of castor trait specific inbred lines under rainfed alfisols of Ananthapuramu - A V S DURGA PRASAD; Y PAVAN KUMAR REDDY; B S REDDY; J JAWAHAR LAL (Journal of Oilseeds Research, 2023)
Identification of elite genotypes necessitates plant breeders to deploy more apt suitable tools for assessing crop performance. Univariate analyses are too narrow and unreliable as they lack considerate relations between variables. Hence the current study with twenty seven trait specific inbred lines of Castor along with four checks viz., 48-1, DCS-107, PCS-124 and PCS-262 were analysed through PCA approach for yield and its attributes during kharif, 2021 at Agricultural Research Station, Ananthapuramu. Two inbred lines viz., ICIRG17-2-7-15-6 and ICIEEGP63-15 were found promising for high seed yield at 90 DAS & 150 DAS interval. ANOVA indicate existence of significant amount of variability among the genotypes for majority of traits studied.